The Effect of Online Banner Design within Instagram to the Purchase Intention of Consumers - Ekaputra, Rizky; Sundjaja, Arta Moro (Interdisciplinary Social Studies, 2023)
Background: Indonesia is infected with COVID-19 in late 2019. Due of the virus's spreading nature, people are likely to reduce direct social interaction and purchase goods, items, and daily requirements online via social media, E-commerce, and Mobile Apps. While the prospect of a global pandemic is horrifying, it may be a chance for businesses to entice customers with visual banner ads on platforms like Instagram. Aim: The purpose of the following paper is to discuss the significance of the utilization of visual design (Online Banners), in addition to the significance of some other aspects, such as the credibility of the advertisement, the message appeal, and the interactivity within the context of online banner design, in terms of shaping and convincing the user's or consumer's intention to make a purchase during an online transaction. Method: The researchers used the quantitative approach. The respondents will be divided into one of four categories using probability sampling. Findings: Customers' purchase intentions on Instagram, one of the most popular social media platforms, are directly impacted by Online Advertising Visual Design. This is discovered through the mediation of Attitude Towards Advertising, which is an important aspect of advertising.